The use of LDS as a tool to evaluate flocculation mechanisms - Rasteiro, M. G. (2007)
Flocculation studies of precipitated calcium carbonate induced by cationic polyacrylamides (C-PAMs) were carried out using light diffraction scattering (LDS). The effect of both polymer charge density and concentration on the flocculation process and on flocs density was investigated. As expected, results show that high charge density C-PAM induces flocculation by bridging and patching mechanisms simultaneously, while medium charge density C-PAM acts mainly according to the bridging mechanism. Consequently, the mass fractal dimensions of the flocs produced by high charge density C-PAM are higher. Results also show the effect of flocculant concentration: flocculation rate decreases and denser flocs are obtained as flocculant concentration increases. The results obtained so far allowed a preliminary quantitative evaluation of flocculation kinetics. In the flocculation curve, two regions corresponding to different kinetics were identified: a first region dominated by particle aggregation and a second region dominated by flocs stabilization. Therefore, LDS is considered a useful tool to evaluate flocculants performance. A strategy was developed that resulted in the use of LDS to retrieve, in a single test, information on the evolution with time of flocs dimension and structure, flocs resistance and flocculation kinetics. All the tests were performed under turbulent conditions similar to the ones prevailing in process equipment.